2022
DOI: 10.1108/jes-05-2022-0311
|View full text |Cite
|
Sign up to set email alerts
|

Financial sector development, trade and income inequality: regional perspectives using evidence from macro and firm-specific data

Abstract: PurposeThe purpose of this study is to firstly, find out does the relationship between finance, trade and income inequality provides matching evidence using the macro- and firm-level data? Secondly, whether a causal relationship from the firm-specific data can be established.Design/methodology/approachThe authors employed a panel data fixed effect regression and two-stage least square (2sls) using key instruments. Their analysis is conducted based on a sub-sample analysis that emphasizes Latin America Region (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Regarding trade openness, it is observed that income inequality is increased by trade openness in developing countries (Ashenafi & Dong, 2023;Dorn et al, 2022;Naanwaab, 2022;Nawab, Bhatti, & Nawaz, 2021). This is due to various reasons like the openness of a country's economy to international trade might cause modifications in its structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding trade openness, it is observed that income inequality is increased by trade openness in developing countries (Ashenafi & Dong, 2023;Dorn et al, 2022;Naanwaab, 2022;Nawab, Bhatti, & Nawaz, 2021). This is due to various reasons like the openness of a country's economy to international trade might cause modifications in its structure.…”
Section: Resultsmentioning
confidence: 99%
“…Using data from both the macro and the business level, Ashenafi and Dong (2023) investigate using a panel data fixed effect regression and a two-stage least square (2SLS) analysis. The conclusion that can be drawn from the analysis of data collected at the macro level is that the influence of trade on income disparity is unfavorable, even though the expansion of the financial sector increases income inequality.…”
Section: Introductionmentioning
confidence: 99%